SPECIFICITY OF THE INJURY OF THE METACARPAL BONES UNDER THE IMPACT OF BLUNT OBJECTS AND ITS CONSEQUENCES (Conferencea, 2022)
In order to identify the features of the formation, course and outcomes of fractures of the wrist bones, and the fracture of the wrist bones in 24 persons, the male field aged 15 to 48 years, who received injuries under various circumstances. It is established that from exposure to blunt objects most often form fractures of the scaphoid (81.8%) bone, fractures of the remaining bones of the wrist are detected relatively less often (18.2%).). In the scaphoid bone, type A fractures are often formed - an incomplete fracture of the waist, relatively less often - types B 2 - a completed fracture of the waist and B 4 - through a scaphoid - perilunar fracture o-dislocation. Frequent types of fractures of other wrist bones are a fracture of the bodies of the semilunar and hook-shaped, intra-articular uncomplicated fractures of the pisiform bone and palmar fracture of the triangular bone.